Analisis UU No. 8 Tahun 1999 Sebagai Perlindungan Hukum Bagi Konsumen Pengguna Uang Elektronik (E-Money) pada Bank Syariah Mandiri - Aulia Passya Fauzi (HUMANIORUM, 2023)
Prospective BSM E-Money card users will not be required to register (unregistered system), which means they do not need to fill in their identity at Bank Syariah Mandiri. However, there are things that need to be considered by prospective BSM E-Money card users, namely that Bank Syariah Mandiri will not replace the balance used by irresponsible parties if the card chip is lost. This is because, in use, starter packs do not require a PIN or signature anymore. So, of course, the law needs to step in to protect electronic money users from risks that may result in major losses for electronic money users. As consumers, electronic money users can refer to legal protection in Article 1 Paragraph 2 of Law Number 8 of 1999 concerning Consumer Protection. The method used for writing this journal is a normative legal method using a qualitative approach. Given that there is no guarantee from the Deposit Insurance Agency (LPS), at least electronic card users are given equal rights and fairness, like a good relationship between ordinary bank customers and issuing banks, especially Bank Syariah Mandiri. Bank Syariah Mandiri is expected to be able to offer agreements in the use of electronic money payment instruments so that electronic money users can know their rights and obligations toward Bank Syariah Mandiri as business actors.